2019
DOI: 10.20471/acc.2019.58.03.19
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Progression of Takayasu’s Arteritis in Infancy: A Case Report

Abstract: -Takayasu's arteritis (TA) affects the aorta and its branches. immunosuppressants are the usual course of therapy, while surgery has been used in acute cases. There is only scant information on TA in infancy, and the nonspecific symptoms in the initial stage of the disease make the diagnosis difficult and delayed, thus increasing the mortality rate. We describe a case of aggressive progression of TA in an infant. This child was the youngest to be affected with the disease as reported in the literature. A 3.5-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Clinical manifestations of TA are nonspecific in infants and children. Fever and inflammation are the most common manifestations, and the abdominal aorta is the most commonly involved vessel [5,[10][11][12][13][14][15]. In our series, eight (80%) cases had fever as the first symptom and most prominent clinical manifestation.…”
Section: Discussionmentioning
confidence: 54%
“…Clinical manifestations of TA are nonspecific in infants and children. Fever and inflammation are the most common manifestations, and the abdominal aorta is the most commonly involved vessel [5,[10][11][12][13][14][15]. In our series, eight (80%) cases had fever as the first symptom and most prominent clinical manifestation.…”
Section: Discussionmentioning
confidence: 54%
“…Clinical manifestations of TA are nonspeci c in infants and children. Fever and in ammation are the most common manifestations; the abdominal aorta is the most commonly involved vessel [10][11][12][13][14][15][16]. In our series, eight (80%) cases had fever as the rst symptom and most prominent clinical manifestation.…”
Section: Discussionmentioning
confidence: 64%
“…Ohigashi et al [33] reported that the incidence of CAD in adult patients with TAK increased with age. In contrast, Shi-Min et al [34] reported that the age of patients with TAK combined with CAL was mostly < 40 years. After multivariate analysis, Wang et al [11] proposed that age at onset, disease course, height, and body mass index (BMI) were risk factors for adult TAK involving the coronary arteries.…”
Section: Discussionmentioning
confidence: 93%